Mycotic Aortic Aneurysm and Infected Aortic Graft After Intravesical Bacillus Calmette-Guérin Treatment for Bladder Cancer. (January 2019) - Lareyre, Fabien; Reverso-Meinietti, Julie; Carboni, Joseph; Gaudart, Alice; Hassen-Khodja, Réda; Raffort, Juliette
Although intravesical therapy with bacillus Calmette-Guérin (BCG) has proven its efficiency in the treatment of early-stage bladder cancer, infectious complications can occur and mycotic aneurysms represent a rare but life-threatening complication. Here, we report the case of an aortic graft infection in a patient with abdominal aortic aneurysm who received BCG instillations for the treatment of bladder cancer. Based on the current knowledge on this rare vascular complication, we discuss factors that may have contributed to its occurrence and review issues to optimize its management and early detection.